The effect of IL-17 blockage on the neutrophil to lymphocyte ratio in patients with axial spondylarthritis: a comparative study with anti-TNF - Yorulmaz, Elem; Geler Külcü, Duygu (The European Research Journal, 2023)
Objectives: This study aims to evaluate the neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) in patients with axial spondyloarthritis receiving different biologic treatments. Methods: The study included 33 axial spondyloarthritis patients (20 males, 13 females) receiving anti-TNF or secukinumab therapy. Patients’ age, disease duration, ongoing therapy duration, serum C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR), neutrophil, lymphocyte and platelet counts, Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) scores, NLR, and PLR were recorded retrospectively. Results: The patients' mean age was 44 years, and the disease's mean duration was 121.55 months. Fourteen (42.4%) patients were receiving secukinumab, 57.6% of the patients were receiving anti-TNF agents. The male/female ratio was 6/8 in the secukinumab group and 14/5 in the anti-TNF group. The ongoing therapy duration was 8 ± 5.1 months for the secukinumab group and 27 ± 27.6 months for the anti-TNF group. Only NLR was significantly higher in the secukinumab group, and there was no other statistical difference between groups. There was no correlation between NLR, PLR, and CRP, ESR, BASDAI. Conclusions: The results of our study show that only NLR is significantly higher in the secukinumab group compared to the anti-TNF group. Hence NLR may be a useful and sensitive parameter in terms of monitoring disease activity.